2001
DOI: 10.1021/jm010061n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Melanocortin NDP-MSH Agonist Peptide Fragments at the Mouse Central and Peripheral Melanocortin Receptors

Abstract: The central melanocortin receptors, melanocortin-4 (MC4R) and melanocortin-3 (MC3R), are involved in the regulation of satiety and energy homeostasis. The MC4R in particular has become a pharmaceutical industry drug target due to its direct involvement in the regulation of food intake and its potential therapeutic application for the treatment of obesity-related diseases. The melanocortin receptors are stimulated by the native ligand, alpha-melanocyte stimulating hormone (alpha-MSH). The potent and enzymatical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
113
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(126 citation statements)
references
References 32 publications
12
113
1
Order By: Relevance
“…2−4 The conserved tetrapeptide sequence has been determined to be important for the ligand binding/molecular recognition and stimulation of melanocortin receptors (MCRs). 5,6 The MCRs are G protein-coupled receptors (GPCRs) that activate the cyclic adenosine monophosphate (cAMP) signal transduction pathway and generate a cascade of intracellular events, which result in physiological responses. Five melanocortin receptors (MC1−5R) have been cloned and characterized.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2−4 The conserved tetrapeptide sequence has been determined to be important for the ligand binding/molecular recognition and stimulation of melanocortin receptors (MCRs). 5,6 The MCRs are G protein-coupled receptors (GPCRs) that activate the cyclic adenosine monophosphate (cAMP) signal transduction pathway and generate a cascade of intracellular events, which result in physiological responses. Five melanocortin receptors (MC1−5R) have been cloned and characterized.…”
mentioning
confidence: 99%
“…6 The melanocortin agonist core peptide Ac-His-Phe-Arg-Trp-NH 2 (2), possessed 130-, 25-, 200-, and 18-fold decreased potency compared to 1 at the mMC1R and mMC3−5Rs, respectively. The tripeptide AcDPhe-Arg-Trp-NH 2 (3) possessed 550-fold decreased activity at the mMC1R compared to 1 and was only able to stimulate the mMC3R, mMC4R, and mMC5R at 40%, 70%, and 70% of the maximum cAMP response, respectively, at 100 μM concentrations.…”
mentioning
confidence: 99%
“…Substitution of Met 4 with norleucine (Nle) and modifying the conformation of Phe 7 to D-Phe in ␣-MSH (see Table 1) yielded a stable subnanomolar agonist named NDP-␣-MSH (20). Additionally, it has been shown that the His-D-Phe-Arg-Trp tetrapeptide alone has nanomolar activity on the MC4R (21). In another study, a truncated analogue of the inverse agonist agouti-related protein was turned into a full agonist by exchanging the binding sequence with His-D-Phe-ArgTrp (22).…”
Section: Obesity Is An Increasingly Important Global Health Problem Tmentioning
confidence: 99%
“…Both α-MSH and ACTH, as well as the other endogenous melanocortin ligands, contain a core His-Phe-Arg-Trp sequence that has been postulated to be important for molecular recognition and receptor stimulation. [35][36][37][38][39] Molecular recognition of peptides by their cognate receptors has been attributed to the ligand pharmacophore, secondary structure, and chemical functionality of the amino acid side chains. One of the most common and important secondary structures found in peptide hormones that stimulate GPCRs is a reverse turn, specifically a β-turn.…”
Section: Introductionmentioning
confidence: 99%